MAKNA SPIRITUAL DI BALIK BANGUNAN ARSITEKTURRUMAH GADANG ISTANA BASA PAGARUYUNG - Resky Annisa Damayanti; Vanessa Vidia Ardyharini (Universitas Trisakti, 2020)
AbstractReligious life in West Sumatera is very strong. Islamic spirituality dominates in WestSumatera because of the large number of Muslims there. Even this has influencedthe daily life of the Minangkabau people. Its strong effect is also a concern, includingby designers and architects. This research aims to explore the spiritual meaning thatinfluences the architectural building of the Big House of Pagaruyung Palace. TheBig House of Pagaruyung Palace was the residence of the family of the Kingdom ofPagaruyung in the 17th century and is known as the beginning of the spread of Islamin West Sumatera. The present of Basa Pagaruyung Palace is a replica building.Nevertheless, the Basa Pagaruyung Palace was still built by maintaining its original form. The method used is descriptive qualitative with cultural approach. In the end, thepurpose of this research is to reveal the facts, meanings, phenomena and circumstancesthat are happening. The results of the study note that there are four architecturalelements of the Big House of Pagaruyung Palace that have spiritual meaning. It can be concluded that the architectural building of the Big House of Pagaruyung Palace wasbuilt with the thought to connect existing architectural elements with nature. The BigHouse of Pagaruyung Palace predominantly uses the analogy of natural organisms.This is in accordance with the concept of the Minangkabau culture ‘Nature Developingbecomes a Teacher’ which is also heavily influenced by Islamic spirituality. AbstrakKehidupan beragama di Sumatera Barat sangatlah kuat. Spiritualitas Islamsangat mendominasi di Sumatera Barat dikarenakan banyaknya pemelukagama Islam di sana. Hal inipun turut mempengaruhi kehidupan sehari-harimasyarakat Minangkabau. Efeknya yang begitu kuat turut menjadi perhatian,termasuk oleh para desainer maupun arsitek. Penelitian ini bertujuan untukmendalami makna spiritual yang berpengaruh terhadap bangunan arsitekturRumah Gadang Istana Basa Pagaruyung. Istana Basa Pagaruyung merupakantempat kediaman keluarga Kerajaan Pagaruyung pada abad ke-17 dandiketahui sebagai awal mula agama Islam tersebar di Sumatera Barat. IstanaBasa Pagaruyung yang ada sekarang merupakan bangunan replika. Meskipundemikian, Istana Basa Pagaruyung tetap dibangun dengan mempertahankanwujud aslinya semula. Metode yang digunakan adalah kualitatif deskriptifdengan pendekatan kebudayaan. Pada akhirnya, tujuan dari penelitian ini adalah mengungkapkan fakta, makna, fenomena, dan keadaan yang sedangterjadi. Hasil dari penelitian diketahui bahwa terdapat empat elemen arsitekturyang memiliki makna spiritual. Dapat disimpulkan bahwa bangunan arsitektur Rumah Gadang Istana Basa Pagaruyung dibangun dengan pemikiran untuk menghubungkan antara elemen arsitektur yang ada dengan alam. RumahGadang Istana Basa Pagaruyung dominan menggunakan analogi organisme alam. Hal ini sesuai dengan konsep kebudayaan Minangkabau ‘AlamTakambang jadi Guru’ yang juga banyak terpengaruh spiritualitas Islam.